Clearance Systems in the Brain, From Structure to Function - Liu, Jiachen; Guo, Yunzhi; Zhang, Chengyue; Zeng, Yang; Luo, Yongqi; Wang, Gaiqing (Frontiers in Cellular Neuroscience, 2022)
As the most metabolically active organ in the body, there is a recognized need for pathways which remove waste proteins and neurotoxins from brain. Previous research has indicated potential associations between clearance system in the brain and pathologic conditions of the central nervous system (CNS), due to its importance, which has attracted considerable attention recently. In the last decade, studies of clearance system have been restricted to glymphatic system. However, removal of toxic and catabolic waste byproducts can’t be completed independently by glymphatic system, while no known research or paper has focused on a comprehensive overview over structure and function of clearance system. This thesis addresses a neglected aspect of linkage between the structural composition and main components as well as the role of neural cell throughout the clearance system, which found evidence that components of CNS including glymphatic system and meningeal lymphatic system interact with neural cell such as astrocytes and microglia in order to carry out vital clearance functions. As a result of these evidence that can contribute to a better understanding of the clearance system, suggestions were identified for further clinical intervention development of severe conditions caused by accumulation of metabolic waste products and neurotoxins in brain such as Alzheimer’s disease (AD) and Parkinson’s disease (PD).